Predictive Factors of Transient Urinary Incontinence Following Holmium Laser Enucleation of the Prostate (HoLEP): Single-Center Experience - Roxana Andra Coman; Thomas Bschleipfer; Nadim Al Hajjar; Bogdan Petrut (Medicina)
Background and Objectives: The aim of this study was to assess the predictive factors associated with transient urine incontinence (TUI) following holmium laser enucleation of the prostate (HoLEP). Materials and Methods: A retrospective analysis was conducted on a prospectively maintained database containing the first 149 consecutive HoLEP cases between June 2022 and December 2023. The study recorded several patient characteristics, and preoperative data such as IPSS score, total gland volume, preoperative catheterization, Qmax, and PVR volume were collected. During the operation, data on total operating time, enucleation time, morcellation time, and weight of enucleated tissue were recorded. Finally, postoperative data were also documented. TUI refers to a patient’s complaint of urine leakage, irrespective of type. Univariate and multivariate logistic regression analyses were performed to determine factors that predict TUI. Results: The study included 119 patients with BPH. Nineteen (15.96%) of them experienced postoperative TUI. Of those 19 patients, 15 (78.94%) recovered within three months from the date of the surgery. In the multivariate regression analysis, increased age (odds ratio [OR], 3.47; 95% confidence interval [CI], 1.56~7.78; p = 0.002), prostate volume ≥ 100 mL (OR 1.86; 95% CI 1.54–2.13; p = 0.001), preoperative PVR volume ≥ 250 mL (OR 1.22; 95% CI 1.10–1.32; p = 0.02), preoperative catheterization (OR, 0.56; 95% CI 0.34–0.78; p = 0.003), increased operation time (OR, 3.87; 95% CI 1.62–4.19; p = 0.002), and resected tissue weight ≥ 40 g (OR, 1.032; 95% CI, 1.015–1.048; p = 0.002) were found to be independent predictors of TUI. Conclusions: The incidence of TUI following HoLEP was found to be 15.96% in patients, with a recovery rate of 78.94% within three months post-surgery. Predictive factors for TUI included age at surgery, prostatic volume, preoperative catheterization, high PVR, longer operative time, and resected tissue weight.